Unsteady state series CSTR modeling of removal of ammonia nitrogen from domestic wastewater treated in a vertical flow constructed wetland - Alejandro Rincón; Gloria Yaneth Florez; Fredy E. Hoyos Velasco (Institute of Advanced Engineering and Science, 2020)
This work shows simulation results for subsurface vertical flow constructed wetland (VFCW) using a series CSTR model. The VFCW considered received the outflow from a domestic wastewater treatment plant. In addition, it was planted with Cyperus sp. and filter media was unsaturated. The model was based on an unsteady state mass balance for ammonia, nitrites, and nitrates, using one to three series CSTRs. Nitrogen transformation mechanisms considered were ammonification, nitrification, plant uptake and denitrification. The following effects were evaluated: the number of reacting CSTRs from one to three; the occurrence of the reaction in second and third CSTRs for the case that three CSTRs hold; the use of either equal or different values of reaction rate parameters between CSTRs; and the discretization of the reaction rate parameters. The inflow and outflow measurements of ammonium, nitrites, and nitrates were used for model calibration. The estimated parameters included the reaction rate coefficients and reactor water volume. The coefficient of determination (R2) evidenced a satisfactory capability of simulating outlet pollutant concentrations. Two and three reacting CSTRs achieved similar R2 value (0.54-0.55), whereas one reacting CSTR achieved an R2 of 0.39, and three CSTRs with reaction only in the first tank achieved an R2 of 0.42. Discretization of the nitrification rate for the case of two reacting CSTRs led to an R2 of 0.94. The parameter sensitivity analysis revealed a significant effect of model parameters on the R2 value.